Accelerated biomethane production from lignocellulosic biomass: Pretreated by mixed enzymes secreted by Trichoderma viride and Aspergillus sp. (August 2020) - Zhao, Xiaoling; Zheng, Zehui; Cai, Yafan; Zhao, Yubin; Zhang, Yue; Gao, Youhui; Cui, Zongjun; Wang, Xiaofen
Graphical abstract: Highlights: Pretreatment is essential for maize straw to accelerate methane production in AD. Enzymatic pretreatment boosted the initial VFAs yield and changed its composition. The highest cumulative methane yield was obtained with a 2/3 ratio of ETv/EAs. Enzymes stimulated the abundance of bacterial related to cellulose degradation. Abstract: Biological pretreatment is a promising technology to increase biogas yield. The methane yield and microbial community resulting from anaerobic digestion of maize straw after pretreatment of enzymes [extracted from Trichoderma viride (ETv) and Aspergillus sp. (EAs)] at different mixing ratios [5/0, 4/1, 3/2, 2/3, 1/4, 0/5] were evaluated. The methane yields from mixed enzymes pretreatment were higher than single enzymes pretreatments of ETv and EAs. The optimal enzymes mixing ratio of ETv and EAs was found to be 2/3, with the cumulative methane yield 512.64 mL/g TSadded, which was 31.74% higher than the control. Enzymatic pretreatment promoted an increase in the abundance of bacteria and archaea associated with cellulose decomposition. The majority of bacteria and archaea were assigned to Bacteroidetes, Firmicutes and Methanosaeta .